Faktor-Faktor Yang Mempengaruhi Minat Berinvestasi Di Reksa Dana Pasar Modal - Sabrinasyah, Ajengesti Latifah; Sipahutar, Ana Pahira; Pratama, Dimas; Siagian, Rani Febrianti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Interest in investing is still minimal because not many people have started investing because there is still a stigma that starting an investment requires large capital and difficult procedures.However, this can change if someone already has an interest in investing, individuals who are interested in investing will prepare themselves as well as possible even though they have limited capital and resources.People who have insight into finance should be moreinterested in investing because they already know what investment decisions to makewhat they will take and have confidence in successfully managing the investmentthe. People can start to invest in some of the wrong sectorsone in the capital market. investment interest among the public is quite high, but not a few from the community arediscouraged whenin his environment, there are many factors that influence why this is soSome of them happened, namely the lack of investment knowledge of the remaining pocket moneywhich can be used for investment and investment education that is stilllimited. This study discusses influencepocket money on public interest in investing. And the influence of education on people's interest in investing.